Logic 101 (#40): Conditional Proofs

preview_player
Показать описание

Conditional proofs allow you to assume that an antecedent is true, derive some consequent, and thereby demonstrate that the conditional statement is true.
Рекомендации по теме
Комментарии
Автор

1. Pv(T-->U)
2. P-->Q
3. ~Sv~Q

4.     S         (The assumption)
5.     ~Q       (3, 4 disjunctive syllogism)
6.     ~P       (2, 5  MT)
7.     T-->U   (1, 6 disj. syll. again)
Therefore: S-->(T-->U)
As in "If we assume S is true, then T-->U must be true."

Thank you fore these videos, I hope to see some more.

SlackwareNVM
Автор

Dude this actually helped me so much thanks

thetitanty
Автор

great job, my professor take an hour to explain this and ended up with the whole class having no idea what he is talking about

tomding
Автор

4. S | Assumption for Conditional Proof
5. ~~S | Line 4 - Double Negation
6. ~Q | Lines 3 & 5 - Disjunctive Syllogism
7. ~P | Lines 2 & 6 - Modus Tollens
8. T => U | Lines 1 & 7 - Disjunctive Syllogism
9. S => (T => U) | Lines 4 - 8 - Conditional Proof

blakeeaton
Автор

THANK YOU SO MUCH. MAY YOU GET ITS REWARD 🙌🏻

fatimashirazi
Автор

Thank you! overall great videos. watched them all. super useful for the paper that i'm currently writing

Автор

1. Pv(T->U)
2. P->Q
3. ~Sv~Q S->(T->U)
4. | S Assumption for conditional proof
5. | ~Q 3.4. Disjunctive syllogism
6. | ~Q-->~P 2. Contraposiiton
7. | ~P 5.6. Modus Ponens
8. | T->U 1.7. Disjunctive syllogism

gidrengidrenovi
Автор

I appreciate these videos but this system you're using is a lot simpler than what seems to be taught in some Logic classes that use a formal Fitch system.
As Fitch does not have syllogism rules. So what took you 8 steps actually requires about 18 when you actually derive the logic behind the syllogism rules

elisha
Автор

If S is true, we can conclude ~Q (3).
If ~Q, we can conclude ~P (2).
If ~P, we can conclude T=>U (1).

Therefore, S => (T=>U)

jvgama
Автор

It could also be proven by using contraposition:



1) P v (T => U)

2)  P => Q

3) -S v -Q

4)      -( T => U)                  Assumption for conditional proof.

5)      1, 4, Disjunctive syllogism.

6)        2, 5 Modus ponens.

 3, 6 Disjuntiv syllogism.

8) -( T=> U) => -S               Conditional proof

9) S=>(T=>U)                     8 Replacement by contraposition.

torosalvajebcn
Автор

This was a bit difficult to grasp at the end. Are we just assuming that the conditional holds by virtue that we tested the assumption in line 4?

reniersteytler
Автор

Question: I thought you can only join S and T=>U through conjunction. Because they are both simultaneously true. So the answer should logically be S^(T=>U) by conjunction. How did you arrive at the conclusion that S=>(T=>U) because that is not the same as S^(T=>U)?

TAEHSAEN
Автор

i thought you only indented for indirect proof

Nay_
Автор

Great videos. Does this mean that by conditional proof, also S=>~P or ~Q=>P or ~Q=>T=>U? Does these mean that anything implies anything below it?

ThemisTheotokatos
Автор

I'm trying to intuitive understand the concept of conditional proof. So, the idea is that when proofing P => Q, we are simply saying that we just want to proof that when P is true, Q must be true, while the other 3 possible combinations of P and Q doesn't matter. Am I right?

DottMySaviour
Автор

i pretty much did it the way shown in the video, except i put in the extra step of switching S to ~~S and then worked from there. but why dont i need to do that?

cannos
Автор

Anybody actually solve this using fitch?

CaptainASD
Автор

(∼A ⊃ B) v (A ⊃ R) ??? This statement solve it?

AnjaliSharma-sgzg
Автор

This proof appears to be incomplete.

1) P ∨ (T ⇒ U)
2) P ⇒ Q
3) ~S ∨ ~Q ∴ S ⇒ (T ⇒ U)

If we assume S is true, we can prove T -> U is also true (video proof)
∴ S ⇒ (T ⇒ U)

The question is, do we need to take an additional step and prove the conclusion when S is false
If S is false, then

S ⇒ (T ⇒ U) is vacuously true as S is false.

paulcarello